THE METHODS OF TEACHING AND LEARNING FIQH IN ISLAMIC BOARDING SCHOOL, ISLAMIC SCHOOL AND PUBLIC SCHOOL - M. Athoillah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
Fiqh is a compulsory subject even becomes the core in education pesantren, madrasah and school, because fiqh will affect the real life of individual or society in worship (mahdhah) as well as in being muamalah. Teaching learning methods of fiqh in schools consists of: bandongan (wetonan) or lecture; sorogan/private; mudzakarah/musyawarah/munadzarah (discussion), tahfidz (memorizing), tathbiq (demonstration/socio drama) and so on. Teaching learning methods in madrasah or school basically are the same as in pesantren with different terms. Teaching learning methods in pesantren are certainly the forerunner of learning methods in madrasah and school, because historically pesantren is the oldest Islamic institution in Indonesia which presence along with the arrival of Islam into the archipelago which is in Perlak, the west coast of Sumatra in the 1st century of Hijriah. The differences of teaching learning system of fiqh on three educational institutions that are characteristics of each institution. In pesantren, fiqh is taught by non-classical systems. Teaching learning is based on the holly book of fiqh (kutub turats) are not regulated in the programmed syllabus, but adhering to the chapters contained in the holly book is examined. In madrasah, fiqh is a separate subject from a clump of Islamic Religious Education (PAI), while at school, fiqh as an integral part of the subject of PAI. In madrasah and schools, teaching learning of fiqh based on the curriculum was assigned by the government as the enactment of the stages of the implementation of the curriculum in 2013 to PAI at madrasah by the Ministry of Religious from July of the academic year 2014/2015 and in schools established by Ministry of Education and Culture and academic year starting in July 2013/2014.